Individual differences in discourse management - Çokal, Derya; Bishop, Jason; Torregrossa, Jacopo; Patterson, Clare; Grice, Martine; Wehrle, Simon; Lialiou, Maria; Repp, Sophie; Seeliger, Heiko; Eisenbeiß, Sonja; von Heusinger, Klaus; Vogeley, Kai; et al. (Frontiers in Communication, 2025)
Every utterance in discourse we produce arises from the interaction of numerous cognitive functions, such as semantic memory, where we store the meanings of words, executive function and working memory as required for maintenance of a discourse goal, and social cognitive abilities, such as mind-reading capacity as required for tuning what we say to what others know or believe. In this way, a single utterance potentially integrates very different cognitive capacities into a basic discourse processing unit. This suggests that discourse processing and management is a very rich phenomenon that requires a multidimensional approach. We propose that a model of discourse management is comprised of three primary components that interact synergistically: (i) dynamicity, (ii) predictability, and (iii) meta-representationality. Cognitive functions play a pivotal role in the underlying processes, contributing to the development and unfolding of discourse. Understanding the correspondence between individual differences in discourse management (i.e., discourse perception and production) and cognitive functions can shed light on the intricate relationship between language and cognition in discourse management, as well as the appropriate psychometric measures to address this complex interaction. This narrative review presents aspects of discourse management, psychometric measures to comprehensively address these aspects. We close with a discussion of challenges and open questions.